Strategy Formulation to Improve Indonesian Tuna Competitiveness - Sandaya, Nandan (Jurnal Ilmiah Kesatuan (JIK), 2001)
Characterized by low technological content, poor productivity, low quality of product, poor human resources ability, low capital input, and low access to market, Indonesian tuna industry is only resources driven. Consequently, Indonesian exports only tuna in raw and semi-processed conditions. In the Japanese prefer Indonesian Big Eye limited only for Japanese who consume fresh tuna for sashimi. In the meantime, the development of tuna product has grown the trade of tuna. Some value-added products are produced and introduced to consumers especially in harvested from Bali adjacent waters for the taste. However, market for fresh tuna is some developed countries in America and Europe. This study was conducted to examine the strategies to find out the alternative solutions that can be applied to solve the Indonesian tuna industry problems by the Government of Indonesian and the tuna entrepreneurs. SWOT analysis was used to identify the environmental assessment of tuna industry to evaluate strengths, weaknesses, opportunities, and threats. Meanwhile, in order to obtain the priority or weight for each element in internal and external factors, Analytical Hierarchy process (AHP) analysis was applied. Data were analyzed using Expert Choice Version 8.0. It is concluded that the Indonesian tuna industry is in the average position, neither too weak nor too strong, both internally and externally. Considering the SWOT analysis, introducing the existing market using comparative advantages, is the best strategy at this moment, before competitive advantages can be increased. Further, the development of tuna added value with the improvement of tuna processing, the increase of the large fishing vessel number, the implementation of clean advance technology, and the improvement of tuna plasma cooperation in order to improve the rural fisheries are the other important strategies that have to be conducted for future competitiveness. Keyword: strategy formulation, competitiveness, analytical hierarchy process, SWOT analysis